2008
DOI: 10.1111/j.1460-9568.2008.06395.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional organization of inferior parietal lobule convexity in the macaque monkey: electrophysiological characterization of motor, sensory and mirror responses and their correlation with cytoarchitectonic areas

Abstract: The general view on the functional role of the monkey inferior parietal lobule (IPL) convexity mainly derives from studies carried out more than two decades ago and does not account for the functional complexity suggested by more recent neuroanatomical findings. We investigated this issue by recording multi- and single units in the IPL convexity of two monkeys and characterizing their somatosensory, visual and motor responses, using a naturalistic (ethologically relevant) approach. These properties were then m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
266
3
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 311 publications
(295 citation statements)
references
References 84 publications
(238 reference statements)
23
266
3
3
Order By: Relevance
“…Mirror neurons are also present in the rostral part of the inferior parietal lobule (Ipl), particularly in area pFG [10][11][12] and the anterior intraparietal area (AIp) 9,13 (FIG. 1).…”
Section: Movementmentioning
confidence: 99%
“…Mirror neurons are also present in the rostral part of the inferior parietal lobule (Ipl), particularly in area pFG [10][11][12] and the anterior intraparietal area (AIp) 9,13 (FIG. 1).…”
Section: Movementmentioning
confidence: 99%
“…The few studies of macaque MNs which report detailed congruency analyses all describe substantial proportions (6-30%) of so-called 'noncongruent' (or 'logically-related') MNs which respond to the observation and execution of different actions (di Pellegrino et al, 1992;Gallese et al, 1996;Rozzi et al, 2008). In addition, they indicate that a significant proportion of macaque MNs (15-65%) are 'ambiguous' in that they respond to the observation or execution of multiple actions (di Pellegrino et al, 1992;Ferrari et al, 2003;Gallese et al, 1996;Rozzi et al, 2008;Umilta et al, 2001). Similarly, the study of sensorimotor units in human participants has revealed large proportions of neurons with both non-congruent and ambiguous sensorimotor properties (Mukamel et al, 2010).…”
Section: Automatic Imitation and The Mirror Neuron Systemmentioning
confidence: 99%
“…However, there is evidence that sensorimotor ambiguity may be a typical feature of the MNS, and not merely a product of laboratory S-R training. Substantial proportions of macaque MNs (di Pellegrino et al, 1992;Ferrari et al, 2003;Gallese et al, 1996;Rozzi et al, 2008;Umilta et al, 2001) and human sensorimotor units (Mukamel et al, 2010) discharge indiscriminately during the observation of multiple actions, or selectively during the observation and execution of different actions. The resulting sensorimotor ambiguity is challenging for theories which posit that MNs make a functional contribution to action understanding (Rizzolatti & Craighero, 2004;Rizzolatti et al, 1996), imitation (Heyes, 2011;Iacoboni, 2009), or generic action selection (Hickok & Hauser, 2010).…”
Section: Implications For the Functioning Of The 'Mirror Neuron System'mentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, the primate PPC was conceptualized as forming an "intentional map" made of distinct subareas for planning movements of the eye, arm or hand (Andersen and Buneo, 2002). Systematic electrophysiological mapping has also shown the existence of graded topographies along the surface of the inferior parietal lobe in monkeys (Rozzi et al 2008). Specifically, a somatotopic organization was found for various motor responses, with movements of the mouth being most rostral, movements of the hand next, and arm movements most caudal.…”
mentioning
confidence: 99%